PERAN NOTASI BALOK DALAM PEMBELAJARAN BIOLA DI LEMBAGA KURSUS MUSIK (Studi Kasus Pembelajaran Lagu Klasik dan Pop di Jogja Music School) - Santy Alif Patuh Briyandewi; Wiwik Sushartami; Gabriel Roosmargo Lono Lastoro Simatupang (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2021)
Classical music notation is a basis for studying Western classical music instruments (including violin) in formal institution with majoring classical music. Based on pre-observation the author knows the classical music notation has undergoing adjustment in non-formal institution (music course), one of them is at Jogja Music School course violin class, so this research will discuss how a classical music notation play a role for students in the violin process in Jogja Music School. This research used a qualitative method with a musicological approach, that is done with observation, interviews, and documentation. Based on the data obtained from two students, it was found that one student played pop songs with classical music notation in different ways (playing improve) and author found the other student played pop songs without classical music notation, therefore in the discussion section the comparative technique is used to analyze the learning process of the two students. The results of this research showed that classical music notation has a role in forming the disciplinary attitude of students in playing a musical piece. The discipline in playing a musical piece includes the discipline of reading rhythm and melody, also discipline in playing the violin technique as written on the score.